PERLINDUNGAN HUKUM TERHADAP BANK ATAS KONFLIK ALAS HAK DARI HAK TANGGUNGAN (STUDI KASUS : PUTUSAN PN MEDAN REGISTER No.113/PDT.G/2006/PN-MDN Tanggal 01-03-2007) - DONALD PADMALI LIE (PREMISE LAW JURNAL, 2013)
ABSTRACT In Addition to the basic principles as a consequence of the legal protection for the Bank as creditor with collateral right as the quarantee, the legal action taken by the Bank for the dispute of basic occured is a somasi to debtor, a law suit against the debtor through State Court Uitvoer Bij Voorad, the execution of court decision, the execution of debt acknowledgment, execution of collateral right, parate of execution of collateral right, execution against the quarantor,  forced-agency institution ang bankruptcy through the Commercial Court. The solution taken by the Bank as the holder of collateral right of the conflicton the basic right functioned as debt quarantee is loan restructuring, facility transfer, and partly or wholly repaymnet of debt. Bank can also fight the State Court back, file a law suit against the plaintiffs, the defendants, National Land Board and the Police who have carried ot the execution of the object served as debt quarantee with a burden of collateral right.   Keywords :  Legal Protection, Bank, Basic Right Conflict, Collateral Right